THE ROLE OF COMPUTER LITERACY IN THE STUDY OF THE TOPIC OF NUMERICAL CHARACTERISTICS OF THE SAMPLE - Raxmonova Nilufarxon Vaxobjon qizi (Journals Park Publishing, 2024)
This article explores the critical role of computer literacy in the study of numerical characteristics of the sample. It examines how proficiency in computer skills enhances the ability to collect, analyze, and interpret sample data. The discussion covers various aspects, including data collection methods, statistical analysis software, and the interpretation of numerical results, highlighting the significance of computer literacy in modern statistical practices.
Keywords: Computer Literacy, Numerical Characteristics, Sample Data, Statistical Analysis, Data Collection, Data Interpretation, Statistical Software.